Determination of water flow rate into subsea deep rock cavern with horseshoe cross-section - Zhao, Zhiye (CPC Press, Taylor and Francis., 2015)
To reduce the risk related to water seepage during tunnel/cavern excavation, some analytical solutions for water inflow prediction corresponding to specific geological conditions have been established over the last decades. Unfortunately, these analytical solutions are only applicable for tunnels/caverns with regular cross-sections, such as circular, elliptical or square. In reality, the cross-sections for most of real tunnels/caverns are always asymmetric, such as in a horseshoe shape. Therefore, the existing analytical solutions are not very suitable for water inflow prediction. Based on the monitoring data from a deep subsea rock cavern with horseshoe-shaped cross-section, and taking the advantages of both the analytical solutions and the numerical method, this paper proposed a semi-analytical approach for determining the water inflow rate. In this paper, the two-dimensional water inflow is described by a simplified linear equation with assumptions of Darcy’s law and mass conservation. According to the monitoring data collected from the site, FLAC 2D is used to validate the correctness of the simplified linear equation, and to determine the constants in the empirical equation. Then, water flow could be estimated by the established semi-analytical solution. The approach presented in this paper offers an effective alternative to predict the water inflow rate for caverns excavated with similar hydrogeological conditions, and provides an back analysis procedure for estimating the hydraulic conductivities for rock cavern projects.